STUDY THE EFFECT OF STRAIN MEASURES OF POST-RESUSCITATE AGING AND AGE AT SLAUGHTER ON BROILER MEAT QULITY - R. S. Al-Mahdawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The purpose of this study was to investigate the relationships between broiler strain, slaughter age, and post-chill (PC) aging duration in terms of measurable meat quality parameters. Two hundred fifty Hubbard on one day old chicks classic and two hundred fifty Lohman were bread in a commercial setting. Each strain had half of its broiler chicks slain at 32 days of age and the other half at 42 days of age. A total of 168 bodies (84 Hubbard and 84 Lohman) were selected at random on each day of processing, with each strain being divided into 28 groups and aged for 0, 4, and 24 hours. Each strain had a comparable average weekly body weight. Hubbard strain animals demonstrated greater feed conversion ratios during weeks two and three of life (P≥ 0.05). A bird’s age had a significant effect (p≥0.05) on initial pH of the carcass, with birds that were 32 days old having lower pH values (41 days old). Carcass temperature of Lohman’s was higher than Hubbard’s at 0h, 2h, and 4h post-PC (p≥0.001). Breast temperature was lower in younger birds throughout all PC assessment intervals (p≥0.001). Stress, age, and aging time had no effect on thaw loss, cook loss, and water holding capacity. Meat of Lohman strain was softer (P≥0.05) than meat of Hubbard strain, and as broiler age and aging time rose, softness also improved. The Hubbard strain produced meat was lighter in color and less red than that of Lohman strain, which came from birds of that darker. It was determined that the breast meat quality features were most affected by strain, slaughter age and PC aging period and that softer fillet could be achieved by maturing for 4 hours before to deboning.